TRANSPORTATION TEST DRY SYSTEM OF JELAWAT (Leptobarbus hoevenii) WITH USING BANANA STEM EXTRACT - Andika Pratama; Dewita Buchari; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was intended to determine the effect of using banana stem extract anesthesia againts the survival rate jelawat (Leptobarbus hoevenii) in the testing pf tranport for 4 hours and to determine the best concentrate of banana stem extract be used as anesthesia on jelawat. The using of research method was descriptive method, of wihch 3 varians were consentrate of banana stem 10%, 15% and 20%. The 15% of banana stem extract 15% that was the superior treatment based on transportation test dry system for 4 hours with the survival rate jelawat was 95% of the total sample. Where is the time required at a concentration of anesthetic 15% to fainting fish average over 35 minutes and requires an average over 40 minutes to be aware of jelawat.Key words: Anesthesia, Banana Stem Extract